Yesus Sebagai Pencerita: Perspektif Sastra Dari Perumpamaan ﻿ - Kistemaker, Simon J. (Veritas : Jurnal Teologi dan Pelayanan, 2004)
Several literary features of Jesus’ parables are noteworthy. In some respects Matthew’s recorded parables differ from Luke’s in presenting colorless sketches. Luke’s parables, on the other hand, are vivid and full of color. Parables in both Gospels, however, are characterized by contrasts. All the parables demonstrate artistry in their unity, coherence, balance, contrast, recurrence, and symmetry. Jesus’ repetition of similar parables on separate occasions illustrates His goal of giving emphasis by way of repetition. By using open-ended parables, Jesus drew His listeners into real-life situations and presented them with the need for a decision on their parts. Allegory in Jesus’ parables brought people into familiar surroundings and highlighted the mercy of God toward sinners. All in all, the parables of Jesus were in a category all their own and were quite distinct from other parabolic teachings in their timelessness and universality.